Development an Augmented Reality-Based Mathematics Application to Improve Junior High School Students' Comprehension of Mathematical Concepts - Putri, Astana Aulia; H, Nurhikmah; Taris, Lu’mu (Universitas Sebelas Maret, 2025)
Mathematics education at the junior high school level faces challenges in helping students visualize three-dimensional geometric concepts using traditional methods. Augmented reality (AR) has been proposed as a potential solution due to its ability to provide interactive 3D representations, yet research on its implementation in Indonesian schools remains limited. This study aims to develop and evaluate an AR-based mathematics application to improve students' conceptual understanding of geometry. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved 45 students in field trials, preceded by individual (5 students), small group (12 students), and large group (20 students) trials. Data were collected through teacher questionnaires, student questionnaires, pre-tests, and post-tests, with instrument validation conducted through expert review. Descriptive and inferential statistical analyses were applied to measure learning effectiveness. The results show a significant improvement in students' ability to visualize geometric concepts, with average scores increasing from 46.31 (pre-test) to 92.91 (post-test). The findings suggest that AR technology can enhance engagement and comprehension in mathematics learning. However, implementation challenges, such as access to AR-compatible devices and teacher readiness, require further study. This research contributes to the integration of AR in mathematics education and highlights its potential for broader adoption in schools with adequate technological infrastructure.